Unilateral submandibular gland aplasia with ipsilateral parotid gland hypertrophy presenting as infra-auricular swelling - Jain, Rupali; Ahuja, Chirag Kamal; Virk, Ramandeep; Singh, Paramjeet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Congenital absence of any one of the major salivary glands is usually asymptomatic per se but may come to the fore during evaluation of a relatively insignificant consequence it may lead to. We report a rare case of unilateral submandibular gland aplasia presenting with a long-standing ipsilateral infra-auricular facial swelling due to compensatory secondary hypertrophy of the parotid gland, which was mistaken as recurrent parotitis. This was evident on computed tomography as an absent right submandibular gland with smooth bulky ipsilateral parotid having no ductal dilatation or periglandular inflammation. An awareness of this etiology, though rare, would be helpful to both the radiologist and the referring physician as it would prevent an unnecessary biopsy of the enlarged parotid and mitigate the scare arising out of the clinical findings of an infra-auricular swelling.